القيم القرآنية الحاكمة للتربية وأثرها في تعزيز الأمن التعليمي - مسرار, حميد (جامعة الوادي - University of Eloued, 2021)
الحمد لله رب العالمين و الصلاة و السلام على أشرف المرسلين أما بعد، فلا خلاف في أهمية التربية في تكوين الإنسان ورسم معالم هويته الحضارية،فهي أهم عملية يخضع لها الإنسان في حياته وعليها يتوقف نموه،وهي سبب من أسباب رقي الأمم ،لذلك فهي تنبثق من فلسفة محكمة تبين للمربين معالم الطريق. وعليه فالقرآن الكريم هو كتاب تربية وتوجيه ،كما هو كتاب عقيدة وعبادة وشريعة وأخلاق، بل هو دستور هذه الأمة ترجع إليه في كل أحوالها ، فهو للمسلم كنز عظيم من كنوز الثقافة الإنسانية ولا سيما الروحية منها ،وهو أول ما يكون كتاب تربية وتهذيب على وجه العموم، وكتاب تربية اجتماعية وأخلاقية على وجه الخصوص، ونظرا لأن فاعلية واستقامة البرامج التربوية وتأثيرها في سلوك الناشئين يعتمد اعتماداً كبيراً على القيم ،فإن الرجوع إلى القرآن باعتباره مصدرا تربويا لا يعتوره نقص سيمكننا من منهاج متكامل إن طبقناه أعطانا الأفضل والأمثل والأكمل، ونظرا لأهمية التربية القرآنية في علاج كثير من الإشكالات القيمية التي أصبحت تعاني منها المجتمعات العربية و الإسلامية فالسؤال العالق : ما القيم القرآنية الحاكمة للتربية؟وما دورها في تعزيز مفاهيم الأمن التعليمي ؟ وقد خلص البحث إلى النتائج الآتية: القيم الحاكمة يمكن إجمالها في أربع وهي: القيم الإيمانية والقيم الإنسانية و القيم االتربوية والتربية العمرانية. وهي قيم تفضي إلى تحقيق الأمن التعلمي،فهي أصل لتحقيق أمن المعلم والمتعلم وهي أساس في المنهاج التربوي وهي مرتكز لتحصيل أمن الفضاء المدرسي. إن القيم القرانية الحاكمة قد تكون علاجا لكثير من الاختلالات والاعتلالات التي ابتليت بها المدرسة عموما من مظاهر العنف وعدم الاحترام وتحطيم وتكسير كل ما يمت بصلة للمدرسة، فما على المسؤولين وأرباب القرار إلا الانتباه إليها وتوعية المجتمع بها As for yet, there is no dispute regarding the importance of education in the formation of the human being and the drawing of the features of his civilized identity, for it is the most important process that a person undergoes in his life and upon which his growth stops, and it is one of the reasons for the advancement of nations, so it emerges from A tight philosophy that shows educators the way. Accordingly, the Noble Qur’an is a book of education and guidance as it is a book of doctrine, worship, law and morals. Rather, it is the constitution of this nation that it refers to in all its conditions, for it is for the Muslim a great treasure of the treasures of human culture, especially the spiritual ones, and it is the first to be a book of education and discipline in general. It is a book of social and moral education in particular, and given that the effectiveness and integrity of educational programs and their impact on the behavior of young people depends greatly on values, so referring to the Qur’an as an educational source without any deficiency will enable us to have an integrated curriculum if we apply it gives us the best, optimal and most complete, and given the importance of Qur’anic education in Treating many of the value problems that Arab and Islamic societies have become suffering from. The unresolved question is: What are the Qur’anic values that govern education, and what is their role in promoting concepts of educational security? The research concluded the following results: The governing values can be summarized in four, namely: faith values, human values, educational values, and urban education. They are values conducive to achieving educational security. They are the basis for achieving teacher and learner security. They are the basis of the educational curriculum and are the basis for achieving school space security. The ruling Quranic values may be a remedy for many of the imbalances and deficiencies that afflict the school in general, including manifestations of violence and disrespect, and the destruction and breakage of everything related to the school.
Quranic values related to education and their impact on strengthening educational security
مقال
Keywords: القيم، القرآن، الأمن ،التعليم ،الأمن التعليمي; Values; Quran; security; education; educational security.